Class Action in the Use of Reading Method to Develop Reading Skill/إجراء صفي في استخدام طريقة القراءة لتنمية مهارة القراءة - Maltuf Anam (JURNAL IJ-ATL, 2018)
Reading is one of important language competent for developed because written language as object of reading which didn’t know about time and place. Reading activity didn’t just express of sound syimbols in the text, but comprehend of good text. That one of weakness of student in first semester State for Islamic Studies Miftahul Ulum Pamekasan which must be improved with look for good method. One of method which was bilieved as appropriate method was reading method. With this method was hoped be able to improve student in reading arabic texts, so that was needed to do the research about increase of reading competent with used  reading method. The purpose of this research was for to know, how used reading method in improve student’s reading competent about arabic text for comprehension aspect which includes; comprehend of meaning text, main idea of paragraph and implied meaning from all texst.القراءة هي واحدة من اللغات الهامة المؤهلة لتطويرها لأن اللغة المكتوبة هي موضوع القراءة التي لا تعرف عن الزمان والمكان. لم يقتصر نشاط القراءة على التعبير عن المقاطع الصوتية السليمة في النص فحسب ، بل فهم أيضًا النصوص الجيدة. تلك نقطة ضعف الطالب في المستوى الأول بقسم الدراسات الإسلامية بجامعة مفتاح العلوم باميكسان التي يجب تحسينها مع البحث عن طريقة جيدة. وتلك الطريقة هي طريقة القراءة. مع هذا الأسلوب كان من المأمول أن يكون قادرا على تحسين الطالب في قراءة النصوص العربية، لذلك كان ضروريًا لإجراء بحث حول زيادة القراءة المختصة بطرائق القراءة المستخدمة. الغرض من هذا البحث هو معرفة كيفية استخدام أسلوب القراءة في تحسين قراءة الطالب المختص حول النص العربي لوجه الفهم والذي يتضمن: فهم معنى النص ، والفكرة الرئيسية للفقرة والمعنى أو المضمون من جميع النصوص.